Nanoclustering in Silicon Induced by Oxygen Ions Implanted - D. Manno; A. Serra; E. Filippo; M. Rossi; G. Quarta; L. Maruccio; L. Calcagnile (Nanomaterials and Nanotechnology)
We report about the nanoclustering induced by oxygen‐implantation in silicon. A tandem‐type accelerator, with a maximum acceleration voltage of 3 MV, equipped with a sputtering ion source suitable for the production of high current ion beams by sputtering of solid cathodes has been used. The surface modifications and the structure of nanoclusters are investigated. The topographic images, obtained by scanning tunnelling microscope showed that the surface is covered with a dense array of tetragonal nanostructures oriented with respect to the substrate. Raman spectroscopy data allowed us to estimate an average cluster size of about 50 nm. Resistivity and Hall effect measurements evidenced that the electron transport in the implanted silicon samples is affected by the nanoclusters array and it could be explained by thermally activated hopping between localized states.